Review of Altay Coşkun (ed.), Ethnic Constructs, Royal Dynasties and Historical Geography around the Black Sea Littoral, Stuttgart, Franz Steiner Verlag (2021) - Raúl Navas Moreno (Karanos)
Review of Altay Coşkun (ed.), Ethnic Constructs, Royal Dynasties and Historical Geography around the Black Sea Littoral, Stuttgart, Franz Steiner Verlag (2021).